Clinical and Radiological Manifestations of Pulmonary Tuberculosis, Jazan Region, Saudi Arabia - Abuobaida Yassin; Heba M. Shalaby (Hail Journal of Health Sciences)
Context: Tuberculosis (TB) is a public health problem worldwide with a wide range of clinico-radiological manifestations. These features can vary and are not specific, which can lead to misdiagnosis and delay in treatment. In Jazan Region, Saudi Arabia (SA), currently, there is no published report on the clinico-radiological manifestations of TB patients. Aims: This study aims to determine the clinico-radiological characteristics of TB among adult patients in the Jazan Region, SA. Settings and Design: This cross-sectional study design was conducted at Jazan Chest Hospital in the Jazan region of SA over 10 months. Materials and Methods: The study included all adults aged 18 years or older who were newly diagnosed with TB. Data were collected using a questionnaire consisting of three sections. The first section collected background information about the study population, the second section recorded presenting complaints and risk factors, and the third section included diagnostic criteria such as microbiological tests and radiological characteristics. Statistical Analysis Used: The data analysis was performed using IBM Statistical Package for Social Sciences software. Descriptive and inferential statistics were used to identify correlations between clinico-radiological manifestations and other variables, with a P value of <0.05 considered statistically significant. Results: A total of 114 patients were enrolled in the study, with an average age of 35.25 ± 17.157 years. The majority of the participants were male (71.1%) and Saudi (43%). Only 42% of the patients were married, whereas 60.5% lived in rural areas. A significant number of patients had only elementary education (42.1%) or were illiterate (28.9%). Most participants had a normal body mass index (77.2%), whereas a smaller percentage were underweight (17.5%) or overweight (5.3%). Various risk factors were reported, including smoking, substance abuse, contact with active TB patients, diabetes mellitus, and a history of TB. Coronavirus disease 2019 symptoms lasted 8 weeks or more for most individuals (73.7%), with weight loss, fever, and sweating being prevalent. Cough was a common respiratory symptom (69.3%), but shortness of breath (SOB) was significantly higher in males than in females. Radiological lesions were mainly located in the upper and middle zones, with consolidation being the most prevalent. Fever was a significant predictor of sputum positivity for alcohol-fast bacilli (AFB), but other symptoms did not show significant associations. General symptoms were more common in patients with non-parenchymal lesions, whereas respiratory symptoms were linked to parenchymal radiological manifestations. The extent of radiological lesions did not correlate with symptom duration. Conclusion: The current revealed a high prevalence of common symptoms (cough, fever, and weight loss) and associations between fever and sputum AFB positivity. Radiologically, parenchymal lesions correlated with cough and SOB, whereas non-parenchymal lesions correlated with hemoptysis. The study highlights the importance of targeted screening, management strategies, and awareness initiatives in this population.